Motivasi Tokoh Eliza dalam Memperjuangkan Hak dan Kebebasan dari Perbudakan dalam Novel Uncle Tom’s cabin karya Harriet Beecher Stowe - Widawati, Indah (LANTERN (Journal on English Language, Culture and Literature), 2012)
This thesis is entitled “ Motivasi Tokoh Eliza dalam Memperjuangkan Hak dan Kebebasan dari Perbudakan dalam Novel Uncle Tom’s Cabin karya Harriet Becheer Stowe”. The aims of this thesis are to analyze the characters of the novel, Eliza, George Harris and Haley. This thesis using a theory of Abraham Maslow which is related with Eliza’s motives. The theory could also be used to know the impact of Eliza’s escape. The method used in textual library research. To get the data, the writer read some books and took some notes related to the topic, either from library research or internet. The conclusion of this thesis shows that Eliza makes a great attempt to gain freedom from slavery.